New contribution to the knowledge of the neotropical species of the genus Astylus (Laporte, 1836) (Coleoptera: Melyridae) - Estrada, Patricia (Zootaxa, 2023)
Fabricius (1775) describes Anobium lineatum for Brazil, a species recognized as Astylus (Melyridae). The study of the external morphology and genitalia of the type material and collections allows us to establish Astylus subacuminatus (Solier, 1849) as a synonym of Astylus lineatus (Fabricius, 1775). Likewise, the varieties described by Pic (1919) A. lineatus var. inlineatus and A. lineatus var. janeirensis are established as new synonyms. A. lineatus is redescribed and types material photographs are provided.